Serum bilirubin level is associated with exercise capacity and quality of life in chronic obstructive pulmonary disease - Leem, Ah Young (Respir Res, 2019)
BACKGROUND: Bilirubin has antioxidant properties against chronic respiratory diseases. However, previous studies are limited by acquisition of serum bilirubin level at one time point and its analysis with clinical parameters. We evaluated the association of serum bilirubin levels with various clinical outcomes of chronic obstructive pulmonary disease (COPD) in Korean Obstructive Lung Disease (KOLD) cohort. METHODS: We included 535 patients with COPD from the KOLD cohort. Serum bilirubin levels and various clinical parameters, such as lung function, 6-min walking (6 MW) distance, quality of life (QoL), and exacerbation, were evaluated annually; their association was analyzed using generalized estimating equations and the linear mixed model. RESULTS: Among 535 patients, 345 (64.5%) and 190 (35.5%) were categorized into Global Initiative for Chronic Obstructive Lung Disease (GOLD) I-II and GOLD III-IV groups, respectively. 6 MW distance was positively associated with serum bilirubin levels, especially in the GOLD I-II group (estimated mean = 41.5). Among QoL indexes, the COPD assessment test score was negatively associated with serum bilirubin levels only in the GOLD I-II group (estimated mean = − 2.8). Higher serum bilirubin levels were independently associated with a higher number of acute exacerbation in the GOLD III-IV group (estimated mean = 0.45, P = 0.001). Multivariate analysis revealed that lung function and mortality were not associated with serum bilirubin levels. CONCLUSIONS: Higher serum bilirubin levels were associated with a longer 6 MW distance and better QoL, especially in the GOLD I-II group, whereas they were related to a higher risk of acute exacerbation, especially in the GOLD III-IV group. Bilirubin levels may represent various conditions in COPD.